2008
DOI: 10.1007/s00018-008-8023-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by polyamines of apoptotic pathways triggered by procyanidins in human metastatic SW620 cells

Abstract: We showed previously that inhibition of polyamine catabolism with the polyamine oxidase inhibitor MDL 72527 (MDL) potentiates the apoptotic effects of apple procyanidins (Pcy) in SW620 cells. Here we report that Pcy caused an activation of the intrinsic apoptotic pathway through enhanced polyamine catabolism and mitochondrial membrane depolarization. MDL in the presence of Pcy caused a profound intracellular depletion of polyamines and exerted a protective effect on mitochondrial functions. MDL potentiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…However, the cellular and molecular mechanisms by which Pcy induce apoptosis in cancer cells are not well understood. Previously, we reported that TRAIL-DR4/DR5 blocking antibodies increased Pcy-triggered apoptosis in SW620 cells 4 . These data suggested the activation of an alternative death pathway.…”
Section: Colomb Med 2011; 42: 166-76mentioning
confidence: 84%
See 3 more Smart Citations
“…However, the cellular and molecular mechanisms by which Pcy induce apoptosis in cancer cells are not well understood. Previously, we reported that TRAIL-DR4/DR5 blocking antibodies increased Pcy-triggered apoptosis in SW620 cells 4 . These data suggested the activation of an alternative death pathway.…”
Section: Colomb Med 2011; 42: 166-76mentioning
confidence: 84%
“…Although Pcy did not overcome the Fas-resistance of SW620 cells, Pcy may activate alternative apoptotic pathways. We have previously shown that Pcy initiated in SW620 cells a cross-talk between the TRAIL (extrinsic) apoptotic pathway and the mitochondrial (intrinsic) apoptotic pathway involving enhanced expression of TRAIL-DR4/DR5 receptors in SW480 and SW620 cells, and activated the polyamine catabolism leading to ROS production, which participated in mitochondria disruption 4,5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However when the two compounds are added together at fixed doses there is a potentiation of the inhibition of ODC compared to the procyanidin treatment alone. There are also significant decreases in the intracellular polyamine pools, particularly in putrescine, spermine and the acetylated forms of the polyamines [19,40]. The combination of MDL 72527 and procyanidins also caused a decrease in the histone deacetylation activity [40].…”
Section: Combination Therapymentioning
confidence: 97%